Faktor-Faktor yang Mempengaruhi Pemanfaatan ATM bagi Nasabah Perbankan (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Islam IAIN Padangsidimpuan) - Lubis, Delima Sari (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
Technological development give positive impact to banking advances. ATM gives convenience for customers, but in fact there are many students of the Faculty of Economics and Islamic Business IAIN Padangsiidmpuan not using ATM. The research used  theory of Acceptable Model Technology (TAM). TAM is based on theory of reasoned action (TRA) which said that a person will receive a computer if the computer provides benefits to the user.Based on the results reseach obtained by regression equation PATM = 9,916 + 0,229Pe + 0,279Tr + 0,033Pr. The value of R square is 0,262 means 26,2% perceived ease of use, trust an perceived risk variables can explain that ATM utlization for students of the Faculty of Economics and Islamic Business IAIN Padangsiidmpuan. For the hypothesis, partially (t test) show that perceived ease of use has tcount t table and significance α (2,4999 1,661 and 0,014 0,1) means perceived ease of use has significant effect  to ATM utilization. Trust has t count ttable (2,655 1,661) significance level α (0,009 0,1) means trust have significant effect  to ATM utilization. Perceived risk has t countt table and significant level α (0,525 1,661 and 0,601 0,1) means  perceived risk has not significant effect  to ATM utilization. While simultaneously (F test) show that perceived ease of use, trust and perceived risk have Fcount F table (12,217 2,14) and significance level is  0,000 α (0,1) means perceived ease of use, Trust and perceived risk simultaneously have significant effect to  ATM utilization.